GE_GERICHTE P/18430/2016 vom 5. Juli 2018 - GE Cour de justice (2018)
ERREUR SUR LES FAITS(DROIT PÉNAL) ; LÉGITIME DÉFENSE ; EXCÈS; LÉGITIME DÉFENSE ; EXCUSABILITÉ ; ÉMOTION | CP.15; CP.16; CP.16.al2; CP.123; CP.183.al1